Refractory Abdominal Pain in a Patient with Chronic Lymphocytic Leukemia: Be Wary of Acquired Angioedema due to C1 Esterase Inhibitor Deficiency. (10th January 2018) - Abdulkareem, Abdullateef; D'Souza, Ryan S.; Mundorff, Joshua; Shrestha, Pragya; Shogbesan, Oluwaseun; Donato, Anthony
Abstract : Acquired angioedema due to C1 inhibitor deficiency (C1INH-AAE) is a rare and potentially fatal syndrome of bradykinin-mediated angioedema characterized by episodes of angioedema without urticaria. It typically manifests with nonpitting edema of the skin and edema in the gastrointestinal (GI) tract mucosa or upper airway. Edema of the upper airway and tongue may lead to life-threatening asphyxiation. C1INH-AAE is typically under-diagnosed because of its rarity and its propensity to mimic more common abdominal conditions and allergic reactions. In this article, we present the case of a 62-year-old male with a history of recently diagnosed chronic lymphocytic leukemia (CLL) who presented to our hospital with recurrent abdominal pain, initially suspected to have Clostridium difficile colitis and diverticulitis. He received a final diagnosis of acquired angioedema due to C1 esterase inhibitor deficiency due to concomitant symptoms of lip swelling, cutaneous nonpitting edema of his lower extremities, and complement level deficiencies. He received acute treatment with C1 esterase replacement and icatibant and was maintained on C1 esterase infusions. He also underwent chemotherapy for his underlying CLL and did not experience further recurrence of his angioedema.